The learning environment of the 21st century: Expectations and reality - Grímsson, Helgi; Sigurðardóttir, Anna Kristín (Icelandic Journal of Education, 2015)
Many school buildings have been constructed in Iceland over the past few decades due to regulations requiring more space for the pupils. The main aim of this study is to investigate the pedagogical assumptions underlying the design of four recent school buildings and how those assumptions have affected teaching practices. In Iceland, as in many other countries, school buildings have been influenced by social and educational needs. Design decisions of architects have been impacted by consultations with different educational specialists for each building site, reflecting different pedagogical ideas at each school institute. Results from a recent Icelandic study indicated a shift in the design of educational buildings. Clusters of classrooms or open spaces, transparent or movable boundaries and public spaces allowing for manifold interactions in flexible groups seemed to have replaced traditional classrooms and confined corridors. It has become a common process to involve many community members when designing a school. In this study, a close look is taken at four school buildings that were designed and opened for use in the 21st century. Two main research questions lead this investigation; what pedagogical ideas underpinned the design process in four schools and how well did they work during the first year in the new building. The four schools were chosen out of a sample of twenty schools from a large scale study on teaching and learning in primary and lower secondary schools, entitled Starfshættir í grunnskólum. This study relies partly on the same sample and partly on the same database. Data was collected specifically for this study through interviews with participants in the design process for each of the four schools; the principal, the architect of the building and a representative from the local educational office. An electronic questionnaire was carried out among all teachers in all twenty schools and classroom observations were conducted in all twenty schools. The interview data was analysed qualitatively ...